Poems that Paint in the Poetry Collection Por Costa Rica de viaje: sus trípticos by Jorge Chen Sham - Vallejos Ramírez, Mayela (2020)
This article presents an analysis of three poems from the collection Por Costa Rica de viaje: sus trípticos, that show how the poetic voice creates a painting with its words capturing not only the scenic space, but also sensations such as smells and flavors. A study of the poetic painting and a reflection of nature from the romantic point of view is made to create a theoretical framework that helps us to better understand the intentionality of the poet. The itinerant poetic voice takes us through different parts of Costa Rica and transmits their emotions through these poems, making us coparticipants in its adventures.